Concept Mastery of Ethnoscience-Based Integrated Science and Life Skills Development of Elementary School Students (Journal of Primary Education, 2019)
Observation in SDN Slawi Kulon 03 shows that concept mastery of the elementary students’ science is still poor and the life skills that are the basic of the students' character have not been fully explored. Students are also still not familiar with the cultural characteristics of their region. This study aims to see the increase in concept mastery of ethnoscience-based integrated science and the development of elementary students' life skills using guided inquiry learning. This experimental study uses the design of one group pre-test - post test. The sample of the research is the fourth-grade students of SDN Slawi Kulon 03 and SDN Blubuk 06 Tegal. The data collection was using observation technique, written test, and documentation. The results show an increase in concept mastery of ethnoscience-based integrated science and the development of life skills significantly when the teacher used guided inquiry learning in both schools.